Usefulness of antibody index assessment in cerebrospinal fluid from patients negative for total-IgG oligoclonal bands - Jarius, Sven; Wildemann, Brigitte (Fluids and barriers of the CNS, 2012)
Testing for cerebrospinal fluid (CSF)-restricted oligoclonal bands (OCB) by isoelectric focusing is used to detect intrathecally produced total IgG. By contrast, antibody indices (AI) are assessed to test for intrathecally produced antigen-specific IgG. A number of previous cases reports have suggested that AI testing might be more sensitive than OCB testing in detecting intrathecal IgG synthesis.